Metagenomic and clinical microbiology. (August 2018) - Amrane, Sophie; Lagier, Jean-Christophe
Abstract: As a result of Next Generation Sequencing methods, metagenomic studies have become increasingly widespread. After being first applied to microbiome description, metagenomics is currently proposed as a diagnostic tool in clinical microbiology, although this application remains confined to the field of research. In this review, we will discuss the application of metagenomics to the detection of bacterial pathogens and demonstrate that the interpretation of the metagenomic results may fluctuate depending on the type of sample analyzed. However, we propose a view of metagenomic application to the evaluation of antimicrobial resistance, epidemic investigations and forensic medicine. Secondly, we present the many limits of metagenomic interpretation and application in routine clinical microbiology. From our perspective, metagenomics is not yet reliable enough for general use in clinical microbiology.